2013
DOI: 10.1534/genetics.113.149443
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Induced Silencing Operates During Opposite-Sex and Unisexual Reproduction in Cryptococcus neoformans

Abstract: Cryptococcus neoformans is a human fungal pathogen that undergoes a dimorphic transition from yeast to hyphae during a-a opposite-sex mating and a-a unisexual reproduction (same-sex mating). Infectious spores are generated during both processes. We previously identified a sex-induced silencing (SIS) pathway in the C. neoformans serotype A var. grubii lineage, in which tandem transgene arrays trigger RNAi-dependent gene silencing at a high frequency during a-a opposite-sex mating, but at an 250-fold lower frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 64 publications
0
30
0
Order By: Relevance
“…Surprisingly, we also found a significant increase in the expression of the T1 and T3 DNA transposons (Table 2). Previous studies have shown that transposable elements are highly expressed during bisexual and unisexual reproduction; however, the RNAi pathway inhibits transposon activity via Sex-Induced Silencing (SIS) and protects the genome against transposition and mutations [44], [45], [46]. Deletion of RDP1 , a component of the RNAi pathway (the RNA-dependent RNA polymerase), induces the expression of retrotransposons during sexual development [44], [46].…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, we also found a significant increase in the expression of the T1 and T3 DNA transposons (Table 2). Previous studies have shown that transposable elements are highly expressed during bisexual and unisexual reproduction; however, the RNAi pathway inhibits transposon activity via Sex-Induced Silencing (SIS) and protects the genome against transposition and mutations [44], [45], [46]. Deletion of RDP1 , a component of the RNAi pathway (the RNA-dependent RNA polymerase), induces the expression of retrotransposons during sexual development [44], [46].…”
Section: Resultsmentioning
confidence: 99%
“…Deletion of RNAi components allows increased expression and movement of transposable elements, which can have direct functional consequences, such as development of FK506 resistance (Wang et al, 2010). Notably, SIS occurs during both bisexual and unisexual mating (Wang et al, 2013b). In addition, the VGII subtype of C. gattii has conspicuously lost its RNAi pathway (Billmyre et al, 2013; D’Souza et al, 2011; Wang et al, 2010).…”
Section: Sex As a Diversity Generatormentioning
confidence: 99%
“…For example, silencing of a tandem insertion of a triplicated SXI2 a - URA5 transgene during a -α opposite-sex reproduction occurs at 250-fold higher frequency than in vegetative mitotic asexual growth. Because C. neoformans can produce spores via two distinct mating pathways: a -α opposite sex and α- α unisexual reproduction, a subsequent study tested and demonstrated that SIS is not limited to a -α opposite-sex but also operates during α- α unisexual reproduction (Wang et al, 2013). More importantly, the silencing frequency observed during opposite-sex and unisexual reproduction is comparable.…”
Section: Introductionmentioning
confidence: 99%
“…In rdp1 mutant strains, siRNAs generated from these repetitive loci were abolished, supporting a role for RNAi in transposon control in C. neoformans . Furthermore, two lines of evidence may explain why C. neoformans evolved a more robust sex-related silencing mechanism (Wang et al, 2010, Wang et al, 2013). First, transposons and retrotransposons are highly expressed during sexual reproduction of RNAi mutant strains.…”
Section: Introductionmentioning
confidence: 99%